ANALISIS RESIPROSITAS PETANI DALAM KEGIATAN USAHA TANI JAGUNG (STUDI KASUS KOMUNITAS PETANI JAGUNG DI DESA MANTOBUA KECAMATAN LOHIA KABUPATEN MUNA) - Rival, Rival; Hamzah, Awaluddin; Arif, La Ode Kasno (Fakultas Pertanian Universitas Halu Oleo, 2023)
The objective of this study is to investigate the form and application of reciprocity among corn farmers in Mantobua Village, Lohia Sub-district, Muna Regency. The informants were selected using the snowball sampling technique, and they were maize farmers who practiced reciprocity in maize cultivation in Mantobua Village. The data were collected through interviews, observations, and documentation using interview guides as instruments. The study employed the qualitative descriptive analysis method, which involves data reduction, data presentation, and conclusion drawing. The results indicate that farmers engage in comparable forms of reciprocity during corn farming activities, such as land clearing, planting, and harvesting. The social reciprocity relationships among corn farmers are increasing, as all farmers continue to engage in reciprocity activities. Reciprocity has been a long-standing practice that continues to this day. Younger farmers still uphold and apply the values of reciprocity to establish social relations between communities.